Peatmoss (Sphagnum) diversification associated with Miocene Northern Hemisphere climatic cooling? - Shaw, A. J. (2014)
Global climate changes sometimes spark biological radiations that can feed back to effect significant ecological impacts. Northern Hemisphere peatlands dominated by living and dead peatmosses (Sphagnum) harbor almost 30% of the global soil carbon pool and have functioned as a net carbon sink throughout the Holocene, and probably since the late Tertiary. Before that time, northern latitudes were dominated by tropical and temperate plant groups and ecosystems.